Basic principles for corrosion control tips based on the electrochemical corrosion cell - Svetomir Hadži Jordanov and Perica Paunović (Society of Chemists and Technologists of Macedonia, 2007)
Corrosion control is an important activity of technical, economical, environmental and aesthetical importance. No matter that corrosion control principles and technological details are established long ago, the practice (especially the protection of capital metallic structures) is not always in accordance with the state-of –the art in this field. So, design procedures seldom contain al necessary steps i.e. design request, specification of corrosion and other exploitation conditions, selection of materials according to their compatibility, sound design of not only mechanics, but also of geometry and surfaces, maintenance details during the entire exploitation period etc. Instead some steps of this procedure are omitted or left to be done by the construction workmanship. In order to elucidate the principles of corrosion control in view of the electrochemical nature of both corrosion process and corrosion protection (CP), a step-by-step procedure is given based on the operation mode of a corrosion cell. In such a way the justification of each CP procedure is made clear. This approach is based on fact that practically every corrosion activity of metals originates in the existence and operation of a corrosion cell and, consequently, all the CP measures are to be based on breaking the electrical circuit of the corrosion cell. The CP modalities known as: i) CP by change in the corrosive medium, ii) CP by change of corroding metal, iii) CP by change of the electrode potential, and iv) CP by means of surface coatings, are given a new meaning as part of a unique concept based on the existence of corrosion cell.